Moderating and mediating factors between servant leadership and turnover intention among bank employees in Pakistan - Sobia, Zeeshan (2020)
The issue of employee turnover and retention has always been a critical element of concern for organizations regardless the nature of the business and its location. Fundamentally, the banking sector of Pakistan have been combating with turnover issue since many decades but still there is lacking of academic research that address the seriousness of this problem specifically. Literature suggests that the positive role of leaders have a powerful influence on reducing the impact of turnover intention in the context of bank employees in Pakistan. However, various types of leadership styles such as; transformational, ethical, authentic and empowering leadership styles have been found to be conducive in reducing turnover intention but amongst all, servant leadership style is considered to be the most influential and creates more variance in positive outcomes (e.g. turnover intention) than any other leadership approach. Servant leadership refers to a leadership approach that focuses on the wellbeing of others and put the organisational concerns as secondary. Data were collected from public and private bank employees through survey questionnaire by using multistage sampling method. SmartPLS was used to analyse the data. This study investigated the key characteristics of servant leadership style as penned by Robert Greenleaf (1977) that servant leaders guide followers to adopt the behaviour of their leaders by putting others need above their own. This study developed and tested a model challenging that servant leaders directly influence turnover intention of bank employees and indirect influence of servant leadership with turnover intention is investigated by testing mediating role of 1) self-efficacy between servant leadership and employee engagement, 2) employee engagement between self-efficacy and turnover intention, 3) psychological ownership between servant leadership and in-role performance, 4) in-role performance between psychological ownership and turnover intention. On top of that, condition in which the direct relationship of servant leadership with turnover intention, employee engagement with turnover intention and in-role performance with turnover intention is identified by modelling distributive justice as a moderator. The results of this study indeed found that 1) The bank managers role of servant leadership directly impact bank employees turnover intention 2) the mediating role of self-efficacy was found to be significant between servant leadership and employee engagement 3) the mediating role of employee engagement was found to be significant between self-efficacy and turnover intention 4) the mediating role of psychological ownership was found to be significant between servant leadership and in-role performance and 5) the mediating role of in-role performance was also found to be significant between psychological ownership and turnover intention relationship. Further, the results of this research showed that the moderating role of distributive justice was only found to be significant in the relationship between inrole performance and turnover intention and insignificant between 1) servant leadership and turnover intention and 2) employee engagement and turnover intention. Theoretically, this study adds value to servant leadership theory, conservation of resource theory and social exchange theory in their applicability in explaining turnover intention. This study is limited to investigate the positive role of leader (i.e. servant leadership style) in reducing turnover intention. Future research may take more broad approach to incorporate negative sides of leadership which include abusive supervision with respect to turnover intention. Moreover, besides distributive justice other dimensions of organisational justice (e.g. procedural justice, interpersonal justice) can also be used to test the moderating effect in this study. Finally, bank managers in Pakistan should encourage their managers in embracing servant leadership style in combating turnover issues.